From the outside looking in : non-members' perspective of NAFTA : an address... to the Wolfgang Friedman Conference on International Law - Bernal, Richard L. ([s.n.] [S.l.], 1992)
Looks at the potential impact of NAFTA; the determinants of impact; and what prospective members of NAFTA would like to see.